Basic Psychological Needs in Exercise Among Adult Exercisers - Emine Çağlar; Murat Uygurtaş (Pamukkale University, 2023)
This study aimed to examine the basic psychological needs in exercise among adult exercisers regarding gender, type of exercise, age groups, and years of exercise. The Basic Psychological Needs in Exercise Scale was administered to 234 adult exercisers (Mage=25.11, SD = 8.89 years). The participants were classified into two age groups (18-29 and 30-45 years) and three groups based on years participating in exercise programs (6 months to less than one year, 1-3 years, and more than three years) and three types of exercise groups (individual, group, and both). We found statistically significant gender and age group differences on the relatedness subscale (p